Pericardial rhabdomyosarcoma in a 9-year old Schnauzer dog - Salinas C., Eben (2020)
The case of a 9-year-old Schnauzer male canine with a history of lack of appetite, lethargy and exercise intolerance is reported. Echocardiography was performed identifying pericardial effusion and a neoplastic mass in the pericardium. The patient presented cardiac tamponade, which was treated with pericardiocentesis. Once the patient was stabilized, a subphrenic partial pericardiectomy was performed, removing the neoplastic mass. The histopathological diagnosis was pleomorphic pericardial rhabdomyosarcoma. The patient had a survival time of 10 weeks. For the present case, the surgical management provided sustained clinical improvement and contributed to the diagnostic process.